ANALYSIS AND DRAINAGE PLANNING IN FLOOD PREVENTION EFFORTS AT MAHROJA COMMERCIAL CENTER TASIKMALAYA - Chairumin Alfin; Heru Setiyo Cahyono; Nur Latifah Khomsiati; Annisa' Carina (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
Drainage analysis and planning in an effort to prevent flooding at the Mahroja Commercial Center Tasikmalaya was carried out with a hydrological analysis method in the Cimulu River Sub-watershed, Tasikmalaya City, to estimate the planned rainfall and flood discharge for the 25-year plan. Daily rainfall data during 2007–2019 from the nearest stations (Cimulu, Cikunten II, Kawalu) were analyzed by arithmetic method to obtain the average rainfall of the area. Statistical frequency analysis was carried out by checking the match of the probability distributions of Gumbel, Log – Normal, and Log – Pearson Type III. Based on the chi-square test, it was obtained that the Type III Log-Pearson distribution provided the best match. The 25-year planned rainfall ranges from 124.48 mm (Normal), 137.74 mm (Gumbel) to 159.33 mm (Log – Pearson). The intensity of peak rainfall was calculated from the IDF (Intensity–Duration–Frequency) curve and used in the Rational method (Q = 0.278· C·I·A) to calculate the plan discharge. The hydraulic model of the regional drainage channel (Mahroja Commercial Center) was made with EPA SWMM 5.1 software (25-year planned rainfall input, DTA 18.8 ha). The results of the SWMM simulation show the value of the planned flood discharge at vital locations (namely: C8 shopping complex of 0.877 m³/s, about 37.8% of the capacity of 2.3196 m³/s; peak in channel C10 of 2.496 m³/s, 59.3% of the capacity of 4.2057 m³/s). This condition indicates that the commercial drainage system is safe against 25 years of flooding. The results of this study are important as a technical basis for flood mitigation in the Cimulu Sub-watershed – namely: planning vulnerable areas and increasing drainage capacity – so that the burden of large rainfall can be reliably overcome.